Implementasi Program Wakaf Di Unit Cabang ACT Duri - Mukhlis Mukhlis; Abdi Sahrial Harahap (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2020)
The existence of ACT in Duri, Bengkalis Regency, is a global humanitarian organization based on voluntarism. In implementing the institution, there are several waqf programs, including renovation of houses of worship and drilled clean water wells for the needs of and helping the poor in the Duri area. This research was conducted with a descriptive approach, namely, interview, observation, interview, and referring to journals related to this research. In this case, it becomes the research subject: Implementation of the Waqf Program while being the object of research at the ACT Duri Branch Unit. The presence of ACT Duri Branch provides a new phenomenon in accommodating the hopes of the community in issuing their assets in the form of waqf, both cash waqf, assets, land, livestock, businesses that have enormous beneficial value for the welfare of the ummah. The programs promoted by ACT Duri Branch focused on renovating houses of worship and drilling wells. The bore well program is implemented to address the educational needs of the pesantren children and the pesantren's surrounding communities who are in dire need given that the clean water conditions in Duri are very uneven and where clean water is located. In this condition, ACT Duri is taking steps to make drilling wells the flagship waqf program in the Duri area.